Fusarium metavorans sp. nov.: The frequent opportunist 'FSSC6'. (10th March 2018) - Al-Hatmi, Abdullah M S; Ahmed, Sarah A; van Diepeningen, Anne D; Drogari-Apiranthitou, Miranda; Verweij, Paul E; Meis, Jacques F; de Hoog, G Sybren
Abstract: The Fusarium solani species complex (FSSC) is the most common group of fusaria associated with superficial and life-threatening infections in humans. Here we formally introduce Fusarium metavorans sp. nov., widely known as FSSC6 ( Fusarium solani species complex lineage 6), one of the most frequent agents of human opportunistic infections. The species is described with multilocus molecular data including sequences of internal transcribed spacer region (ITS), portions of the translation elongation factor 1-a gene ( TEF1 ), and the partial RNA polymerase II gene ( rPB2 ). A phylogenetic approach was used to evaluate species delimitation. Topologies of the trees were concordant. Phylogenetic analyses suggest that the FSSC consists of three major clades encompassing a large number of phylogenetic species; Fusarium metavorans corresponds to phylogenetic species 6 within FSSC clade 3. The species has a global distribution and a wide ecological amplitude, also including strains from soil and agents of opportunistic plant disease; it was also isolated from the gut of the wood-boring cerambycid beetle Anoplophora glabripennis .